(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Conditions leading to emergence of Internet-shortenings, specifics of their structure, semantic content and functioning in Internet space have been studied. Different types of shortenings serve as a means of emotional and artistic expression, and Internet users are showing remarkable ingenuity and imagination here. The author identifies the psychological and psycholinguistic aspects of their spreading in internet-communication. The necessity to study, master and actively use the abbreviations as an effective means of language economy is emphasized. Their structural and semantic features have been described as well. Two groups of abbreviations: lexical and graphical, have been analyzed. Specific attention has been paid to numeric, alphanumeric abbreviations and initialisms. Specific forms of shortenings are used in messages: word replacement, letters and numbers homonymic in sounding to parts of words. Shortenings perform help to save time spent in network, increase the expressiveness of the text. Language of internet users is differentiated by age and profession, level of mastering computer technologies, users’ interests and activities. Here we find programmers, web-designers, system engineers, hackers, gamers, etc. Each group of users uses certain shortenings that may be familiar to other groups in part or not familiar at all. Theoretical conclusions are backed up by relevant factual material.